Transient Pressure Behavior of a Horizontal Well in a Naturally Fractured Gas Reservoir with Dual-Permeability Flow and Stress Sensitivity Effect. (30th April 2022) - Wang, Guiqin; Zhang, Rui; Cui, Liangliang
Abstract : Dual-permeability flow and stress sensitivity effect are two fundamental issues that have been widely investigated in transient pressure analysis for horizontal wells. However, few attempts have been made to simulate the combined effects of dual-permeability flow and stress-dependent fracture permeability on the pressure transient dynamics of a horizontal well in a naturally fractured gas reservoir. In this approach, an analytical model is proposed to integrate the complexities of pressure-dependent PVT properties, dual-permeability flow behavior, and stress-dependent fracture permeability characteristics. The nonlinearity of the mathematical model is weakened by using Pedrosa's transform formulation. Then, the Laplace integral transformation and separation of variables are applied to solve the model. Based on the solution of the mathematical model, a series of new-type curves are drawn to make a precise observation of different flow regimes. The main differences between the proposed model and the traditional models are discussed, and the effects of the permeability modulus of fractures, storability ratio, interporosity flow factor, and skin factor on transient pressure response are also examined. The results show that there are obvious differences in transient pressure dynamic curves between the proposed model and traditional models. The stress sensitivity effect plays a significant role in the intermediate flow period and the late-time pseudoradial flow period. The dual-permeability flow behavior mainly affects the early transient and interporosity flow stages. The proposed model can accurately simulate the transient pressure behaviors of a horizontal well in a naturally fractured gas reservoir with a dual-permeability flow and stress sensitivity effect. The novel model can be used to interpret pressure signals with accurate matching results and more reasonable interpreted parameters.